#### Answer

LCD=5(x-6)(x-6)=5$(x-6)^{2}$

#### Work Step by Step

$\frac{8x^{2}}{(x-6)^{2}}$, $\frac{13x}{5x-30}$
$(x-6)^{2}$=(x-6)(x-6)
5x-30=5(x-6)
LCD=5(x-6)(x-6)=5$(x-6)^{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

LCD=5(x-6)(x-6)=5$(x-6)^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.